Developing an Antiviral Drug Screening System for Anti-Bovine Viral Diarrhea Virus (BVDV) Therapies - Mokhtari, A.; Mahzounieh, M.; Madadgar, O.; Ghalyanchi Langeroudi2, A. (Journal of the Hellenic Veterinary Medical Society, 2019)
Bovine viral diarrhea virus (BVDV) is an economically important animal pathogen affecting cattle. Despite the use of vaccination, test and slaughter practices, BVD remains a serious problem of cattle breeding. This study was conducted in order to develop a cell line that expresses some of BVDV sub-replicons. BVDV-NADL NS3 and 5’UTR were cloned in pWPI-linker B lentiviral plasmid at the upstream of EGFP gene. Consequently, lentiviral vectors containing BVDV-NS3 and BVDV-5’UTR were produced by using the second-generation lentiviral packaging system. By these lentivectors, MDBK cells expressing BVDV-5’UTR and BVDV-NS3 partial fragments were prepared. The efficiency of the infection was evaluated by fluorescence microscopy, western blotting, and RT-PCR. The results indicated that the development of MDBK cell line expressing these transgenes provides a very sensitive antiviral drug screening system for anti-bovine viral diarrhea virus (BVDV) therapies.